(untitled) (Journal of Applied Oral Science, 2014)
Objective: Enterococcus faecalis (E. faecalis) is the most frequently isolated strain in failed endodontic therapy cases since it is resistant to calcium hydroxide (CH). Whether a combination of CH and chlorhexidine (CHX) is more effective than CH alone against E. faecalis is a matter of controversy. Thus, the aim of this study was to conduct a systematic review and meta-analysis of the literature. Material and Methods: A comprehensive search in PubMed, EMbase, EBSCOhost, The Cochrane Library, SciELO, and BBO databases, Clinical trials registers, Open Grey, and conference proceedings from the earliest available date to February 1, 2013 was carried out and the relevant articles were identified by two independent reviewers. Backward and forward search was performed and then inclusion and exclusion criteria were applied. The included studies were divided into "comparisons" according to the depth of sampling and dressing period of each medicament. Meta-analysis was performed using Stata software 10.0. The level of significance was set at 0.05. Results: Eighty-five studies were retrieved from databases and backward/forward searches. Fortyfive studies were considered as relevant (5 in vivo, 18 in vitro, 18 ex vivo, and 4 review articles). Nine studies were included for meta-analysis. Inter-observer agreement (Cohen kappa) was 0.93. The included studies were divided into 21 comparisons for meta-analysis. Chi-square test showed the comparisons were heterogeneous (p